First, put all your variables on the left side. To do that, subtract 3m from both sides.
m-3m -12 = 3m-3m + 4
-2m -12 = 4
Then move all your non-variables to the right side. To do this, add 12 to both sides.
-2m -12 + 12 = 4 + 12
-2m = 16
Then divide by negative two, to get:
m = -8.
That's your answer.
2006-10-16 13:14:18
·
answer #1
·
answered by Bramblyspam 7
·
0⤊
0⤋
You need to combine the like variables - so all the "m"s and the numbers.
So...
m-12 = 3m + 4
You need to bring all the "m"s to one side and the numbers to the other
m - 12 - m = 3m + 4 - m
-12 = 3m - m + 4
-12 = 2m + 4
-12 - 4 = 2m + 4 - 4
-16 = 2m
Then simplify by dividing each side by 2 to find the value of m
-16/2 = 2m/2
-8 = m
To check this answer, plug m=-8 back into the original equation:
m-12 = 3m + 4
(-8) - 12 = 3(-8) + 4
-8 - 12 = -24 + 4
-20 = -20
2006-10-16 20:21:33
·
answer #2
·
answered by Kayla 3
·
0⤊
0⤋
Put the m's together on one side: (subtract m from each side)
m - 12 - m = 3m + 4 - m => -12 = 2m + 4
Put the numbers on the other side (subtract 4 from each side)
-12 - 4 = 2m + 4 - 4 => -16 = 2m
Make the coefficient of m 1 (divide by 2)
-16/2 = 2m/2 => -8 = m
Start on the next problem.
2006-10-16 20:14:17
·
answer #3
·
answered by sofarsogood 5
·
0⤊
0⤋
Hopefully this isnt too confusing
m-12=3m+4
-m -m
-12=2m+4
-4 -4
-16=2m
(divide 2)
m=-8
Hope that helps
2006-10-16 20:16:07
·
answer #4
·
answered by Kelly*Ann 2
·
0⤊
0⤋
1st u add 12 to both sides:
m-12=3m+4
+12 +12
which comes out to be:
m=3m+16
then u subtract 3m from both sides:
m=3m+16
-3m -3m
which is:
-2m=16
which equals:
-8
2006-10-16 21:02:53
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
subtract 4 from both sides which is going to give u this
m - 12 = 3m +4
-4 -4
this is going to give u this
m - 16 = 3m
then subract m from both sides
m - 16 = 3m
-m -m
this is going to give u this
-16 = 2m
then divide by 2
-16/2 = 2m/2
this is going to give u the final answer which is
-8 = m
2006-10-16 20:42:59
·
answer #6
·
answered by First L 1
·
0⤊
0⤋